2011
DOI: 10.1186/1471-2261-11-78
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein is an independent predictor for carotid artery intima-media thickness progression in asymptomatic younger adults (from the Bogalusa Heart Study)

Abstract: BackgroundConflicting information exists regarding the association between hsCRP and the progression of early stages of atherosclerosis. The purpose of the study was to investigate the association of high sensitiviy c-reactive protein (hsCRP) along with major cardiovascular (CV) risk factors on early carotid atherosclerosis progression in a large, population-based cohort study.MethodsThe study cohort included 839 young adults (aged 24 to 43 years, 70% white, 42% men) enrolled in Bogalusa Heart Study, who in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
(29 reference statements)
3
16
1
Order By: Relevance
“…Since hs-CRP is considered to be a sensitive marker of inflammation, a raised hs-CRP level in type 2 diabetic patients may suggest that inflammation could be involved in the pathogenesis of diabetes and early atherosclerotic processes. We observed a positive correlation between C-IMT and hs-CRP, which is in concordance with Toprak and colleagues, who found that any increase of hs-CRP was associated with C-IMT progression independent of other cardiovascular risk factors [Toprak et al 2011]. The INVADE study looked at the association between hs-CRP and C-IMT progression in elderly patients and found an independent association between the two parameters [Sander et al 2007].…”
Section: Carotid Intima Media Thickness (C-imt)supporting
confidence: 91%
“…Since hs-CRP is considered to be a sensitive marker of inflammation, a raised hs-CRP level in type 2 diabetic patients may suggest that inflammation could be involved in the pathogenesis of diabetes and early atherosclerotic processes. We observed a positive correlation between C-IMT and hs-CRP, which is in concordance with Toprak and colleagues, who found that any increase of hs-CRP was associated with C-IMT progression independent of other cardiovascular risk factors [Toprak et al 2011]. The INVADE study looked at the association between hs-CRP and C-IMT progression in elderly patients and found an independent association between the two parameters [Sander et al 2007].…”
Section: Carotid Intima Media Thickness (C-imt)supporting
confidence: 91%
“…There are some reports, however, indicating that the progression of mean IMT in asymptomatic young adults varies from 0.015 to 0.029 mm/year. 25 Furthermore, we collected the present data from untreated and middle-aged individuals, who might be substantially more susceptible to IMT progression. 26 Taken together, we could say that the current data regarding the annual increase of mean IMT of around 0.030-0.050 mm might be within reasonable range.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies have suggested that serum levels of tumor necrosis factor-α, interleukin-6, and C-reactive protein are elevated in patients with congestive heart failure, regardless of the etiology of the condition. Furthermore, elevated blood levels of these inflammatory markers correlate with worsening functional class, increased hospitalization rates, and poorer survival 3538. In addition, structural and functional changes have been observed in the arteries of children with a familial predisposition for AD, and these changes are associated with groups of inflammatory factors and oxidation markers.…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%